Detection of perimacular red dots and blots when screening for diabetic retinopathy: Refer or not refer?. (July 2018) - Baltatescu, Anatolie; Striglia, Elio; Trento, Marina; Mazzeo, Aurora; Cavallo, Franco; Charrier, Lorena; Porta, Massimo
Purpose: Detection of microaneurysms and/or microhaemorrhages near the fovea when screening for diabetic retinopathy poses a problem because referral to retinal specialists may alarm patients and unnecessarily burden ophthalmologists. Methods: Six-month prospective study of patients found to have minimal red lesions within one disc diameter of the fovea when screened for diabetic retinopathy. Two 45° digital photographs, one centred on the macula and the other nasal including the optic disc, were taken for each eye. All patients received a 6-month re-screening appointment. Results: Out of 70 patients, 41 returned for re-screening. Diabetic retinopathy had worsened in 3 who required referral but no treatment, was unchanged in 19 and was undetectable in the other 19. Haemoglobin A1c decreased from 7.76% ± 1.50% (61.3 ± 16.2 mmol/mol) to 6.93% ± 1.7% (52.3 ± 18.9 mmol/mol) in the patients in whom diabetic retinopathy worsened but did not change in the other groups. Baseline haemoglobin A1c ( p = 0.048) and systolic blood pressure ( p = 0.007) were lower in the patients in whom diabetic retinopathy improved, but a multivariate model including haemoglobin A1c, blood pressure and known disease duration could not identify any independent risk factor. Conclusion: Minimal red lesions near the fovea, though commanding early re-screening, do not require immediate referral to retinal specialists.